Editorial - Solihu, Abdul Kabir Hussain (IIUM Press, 2013)
The form of governance that a Muslim majority country should take, given the socio-historical and geographical conditions prevalent in our time, is a question which has attracted the interest of Muslim thinkers. In Southeast Asia, in particular, two modalities of government have been hotly debated: the secular and the Islamic.